From knowledge to action: Participatory research methods to create an action plan for healthier communities - Eva Purkey; Susan A. Bartels; Rifaa Carter; Sophy Chan-Nguyen; Michele Cole; Colleen M. Davison; Meghan Ford; Logan Jackson; Bruce Knox; Autumn Watson; Imaan Bayoumi (PLoS ONE, 2026)
Introduction There is a large knowledge to implementation gap in traditional research. Community based participatory research (CBPR) can fill this gap by improving the validity and relevance of research and by ensuring more effective knowledge translation. CBPR methods can also be used to develop research, policy and programming agendas which can direct the priorities of funders, policy- and decision-makers. The purpose of this paper is to describe the methodology used in a “community engaged” CBPR action planning process, as well as to discuss whether this is an effective method of closing the knowledge to implementation gap. This methods paper illustrates phase two of a CBPR study, the overarching objective of which was to explore how to improve resilience and well being for families facing adversity. Methods Using the research findings from a mixed methods multiple case study exploring families’ experiences of adversity and resilience (phase one), as well as extensive community consultation involving over 250 community members, and a CBPR team of 4 academic and 4 community researchers and a research manager, this study employed novel team-based adaptation of reflexive thematic analysis techniques using CBPR principles to develop participatory, evidence-based community action planning. Results Over 250 community members participated a total of 11 community meetings as part of the consultation process, producing over 200 action items which the research team then collaboratively organized in 20 final topic areas or themes. Multipronged knowledge translation techniques (infographics, websites, policy briefs) ensured that these findings were communicated back to the community, funders, municipal government and other agencies involved in program planning. Conclusion In this context, CBPR was an effective method of engaging a significant number of community members in informing policy, program and research priorities that can improve the lives of people experiencing adversity. Decision makers and program developers demonstrated interest in research findings that involve community participation and consultation by including these findings in subsequent funding applications and referencing them in policy documents. CBPR also led to increased trust and partnership between academic and community organizations as demonstrated by a number of subsequent requests for research training and research partnerships which may benefit all parties in the long run.